Structure-guided engineering and molecular simulations to design a potent monoclonal antibody to target aP2 antigen for adaptive immune response instigation against type 2 diabetes - Khan, Abbas; Zahid, Muhammad Ammar; Mohammad, Anwar; Agouni, Abdelali (Frontiers in Immunology, 2024)
Diabetes mellitus (DM), considered the oldest chronic disease, is a growing public health concern that requires novel innovative therapeutic approaches to improve clinical outcomes. Thus, in the current study, we used graph signature-based approaches combined with molecular simulation and free energy calculation to engineer the CA33, a monoclonal antibody, to target aP2 antigen and produce a robust immune response. Our results revealed that from a mutational landscape of 57 mutants, only five substitutions demonstrated significant results. The molecular docking experiments revealed that T94M, A96E, A96Q, and T94W showed higher docking scores compared to the wild-type. These findings were further confirmed by the calculation of the dissociation constant (KD) which revealed a similar trend. Moreover, molecular simulation analysis demonstrated that the T94M was the most stable complex during the simulation and that internal fluctuations were stabilized upon the binding. The principal components analysis (PCA) revealed that the wild-type and T94Met presented alike behavior of constraint and restricted motion in each PC. The free energy landscape revealed a single metastable for all the complexes during the simulation which shows that the systems do not readily transit through multiple conformations. It shows limited structural variability which underscores the therapeutic efficacy of the antibody against aP2. To provide conclusive evidence, we calculated the total binding free energy (TBE) for each complex which revealed TBE values of -279.84 kcal/mol for the wild-type, -295.22 kcal/mol for the T94M, -281.67 kcal/mol for the T94W, -289.44 kcal/mol for the A96Q, and -277.29 kcal/mol for the A96E. The contribution of the key residues was observed to be conserved across all the complexes. The T94M substitution is the most favorable one and will be useful in guiding rationale antibody designing against diabetes.